Contact‐Force Recovery Can Predict Cardiac Perforation during Radiofrequency Ablation. Issue 9 (4th May 2014) - NAZERI, ALIREZA; GANAPATHY, ANAND; MASSUMI, ALI; MASSUMI, MEHRAN; CONSTANTINE, GARTH; RAZ, SHAUL; RAZAVI, MEHDI
<x xml:space="preserve">Abstract</x> Background During radiofrequency ablation (RFA), the ability to know whether a steam pop has led to cardiac perforation (CP) would be of profound clinical significance. We aimed to determine whether catheter contact‐force characteristics can predict whether a steam pop during RFA causes CP. Methods We used a 7.5F Thermocool® Smarttouch™ force‐sensing catheter (Biosense Webster Inc., Diamond Bar, CA, USA) to perform open‐chest left atrial RFA under direct visualization in four sheep. We measured the contact force and its direction every 50 ms during RFA. At each steam pop, we noted whether CP occurred. We then analyzed the contact‐force signals to determine whether specific features predicted the presence (+) or absence (−) of CP. Results A total of 24 steam pops occurred; 10 were CP+ and 14 were CP−. At the time of CP+ and CP− events, the contact force was 50 ± 25 and 40 ± 15 g, respectively (P = 0.146). All steam‐pop events were associated with a rapid drop‐off in contact force, but 10 of the 14 CP– events showed an immediate contact‐force rebound, whereas none of the CP+ events did. This rebound presumably occurred as the catheter tip resumed contact with the left atrial wall. The average contact‐force rebound equaled 80–100% of the contact‐force drop‐off. Conclusions The ability to measure catheter contact force during RFA is a valuable asset, as contact‐force recovery may be used to predict CP. Further studies are warranted to validate our findings in the clinical setting.